The system of the Catocalinae - a historical survey (Lepidoptera, Noctuidae). - Kühne, Lars; Speidel, Wolfgang (Contributions to Entomology = Beiträge zur Entomologie, 2004)
The present paper reviews the family-group names of the Catocalinae subfamily within the Noctuidae (Lepidoptera). The underlying concepts and their historical evolution to date are described. All known family group names which were assigned within the Catocalinae are listed. New status: Anumet[ini] Wiltshire, 1976 stat. rev., new synonyms: Lagopter[idae] Kirby, 1897 syn. nov. of Dysgoni[idae] Moore, [1885] 1884-7; Lygephil[ini] Wiltshire, 1976 syn. nov. of Toxocamp[idae] Guenée, 1852; Mocis[ini] Berio, 1992 syn. nov. of Remigi[idae] Guenée, 1852; Pangrapt[inae] Grote, 1882 syn. nov. of Focill[idae] Guenée, 1852; Phaeocym[ini] Grote, 1890a syn. nov. of Omopter[idae] Grote, 1895. Nomenclatural ActsAnumet[ini] Wiltshire, 1976 (Noctuidae), stat. rev. previously treated as synonym of SynediniLagopter[idae] Kirby, 1897 (Noctuidae), syn. n. of Dysgoni[idae] Moore, 1885Lygephilini Wiltshire, 1976 (Noctuidae), syn. n. of Toxocamp[idae] Guenée, 1852Mocis[ini] Berio, 1992 (Noctuidae), syn. n. of Remigi[idae] Guenée, 1852Pangrapt[inae] Grote, 1882 (Noctuidae), syn. n. of Focill[idae] Guenée, 1852Phaeocym[ini] Grote, 1890 (Noctuidae), syn. n. of Omopter[idae] Boisduval, 1833